A FEMININE ODYSSEY: UNVEILING DRAUPADI’S COMPLEXITY IN SAI SWAROOPA IYER DRAUPADI: THE TALE OF AN EMPRESS - Suchi Chauhan (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Sai Swaroopa Iyer’s Draupadi: The Tale of an Empress reimagines the epic tale of Draupadi, a central figure from the Mahabharata, by offering a fresh perspective on her multifaceted character. Traditionally depicted as a symbol of strength and resilience, Iyer explores deeper into Draupadi’s emotional and psychological complexity, portraying her as not just a queen and warrior but also a woman struggling with personal dilemmas, vulnerabilities, and conflicting duties. This narrative explores the themes of power, justice, and identity through Draupadi’s relationships with the Pandavas, her own desires, and the expectations imposed by society. Iyer presents Draupadi’s journey as an odyssey of self-realization, highlighting her intellectual sharpness and unwavering conviction in the pursuit of truth. The novel deconstructs traditional portrayals of Draupadi, shedding light on her internal battles and the societal norms that restrict her agency. The book invites readers to reconsider her role in the Mahabharata, emphasizing her human dimensions rather than solely her mythic status. Through this reimagined version, Iyer challenges existing paradigms, offering Draupadi as a symbol of empowerment and resilience, while acknowledging the complexities of her personhood beyond the iconic portrayal in epic texts.